Difficulties in diagnosing a rupture of the left dome of the diaphragm - A. I. Beznosov; V. V. Ivlev; G. I. Ibragimov; A. S. Patsan (Вестник хирургии имени И.И. Грекова)
Rupture of the diaphragm dome in severe combined trauma is an infrequent phenomenon. At the same time, untimely diagnosis in the acute period leads to various serious complications. The article presents a clinical case of treatment of a patient after a severe railway injury, when a rupture of the left dome of the diaphragm with gastric dislocation was not recognized for 4 months. Pain syndrome due to the patient’s empyema of the pleura and necrosis of the stomach wall was stopped for a long time by taking strong drugs.